The maze of bones - Riordan, Rick (39 clues, 2008)
Minutes before she died Grace Cahill changed her will, leaving her descendants an impossible decision: "You have a choice - one million dollars or a clue." Grace is the last matriarch of the Cahills, the world's most powerful family. Everyone from Napoleon to Houdini is related to the Cahills, yet the source of the family power is lost. 39 clues hidden around the world will reveal the family's secret, but no one has been able to assemble them. Now the clues race is on, and young Amy and Dan must decide what's important: hunting clues or uncovering what REALLY happened to their parents.